EMPIRICAL STUDY OF CUSTOMER SATISFACTION AND CUSTOMER LOYALTY: THE ROLE OF INNOVATION CAPABILITY AND ETHICAL BEHAVIOR - Nurul Hidayati; Zainurrafiqi Zainurrafiqi (Al-Amien Prenduan for Islamic Institute, 2020)
Banking sector need to find the right strategy in providing Customer Satisfaction and increase Customer Loyalty. Based on previous empirical research, this study emphasizes the importance of Innovation Capability and Ethical Behavior as the antecedents of Customer Satisfaction. Data were collected from 200 customers of Bank in Pamekasan regency and analyzed using Structural Equation Model (SEM). The major findings include first, Innovation Capability has significant effect on Customer Satisfaction. Second, Ethical Behavior has significant effect on Customer Satisfaction. Third, Customer Satisfaction has significant effect on Customer Loyalty.